Overview of Prosocial Behavior for Student SMK Sepuluh Nopember at the Sidoarjo : Gambaran Perilaku Prososial Pada Siswa SMK Sepuluh Nopember di Sidoarjo - Evi Nabella; Effy Wardati Maryam (Academia Open, 2025)
General Background: Prosocial behavior plays a crucial role in adolescent social development and character formation within educational settings. Specific Background: In vocational high schools, students’ social interactions reflect helping, sharing, cooperating, honesty, and generosity, which contribute to a positive school climate. Knowledge Gap: However, empirical data describing the level and distribution of prosocial behavior among vocational high school students remain limited, particularly in specific institutional contexts. Aims: This study aims to describe the prosocial behavior profile of students at SMK Sepuluh Nopember Sidoarjo. Results: Using a quantitative descriptive design with proportional stratified random sampling, the findings indicate that students’ prosocial behavior generally falls within the moderate category. The helping and cooperating aspects show the highest percentages, while sharing appears at a relatively lower level compared to other dimensions. Novelty: This research provides a context-specific empirical mapping of prosocial behavior among vocational students using a structured multidimensional approach. Implications: The findings offer practical considerations for guidance and counseling programs and character education strategies to strengthen positive social engagement among students in vocational education setting Keywords: Prosocial behavior, Adolescents, Vocational High School Students, Character Education, Quantitative Descriptive Study Key Findings Highlights: Students demonstrate a moderate overall level of social-oriented actions. Cooperative and helping tendencies dominate the observed dimensions. Sharing-related actions appear less frequent compared to other indicators.